2015
DOI: 10.1016/j.pharmthera.2015.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Cdc20 as a novel cancer therapeutic strategy

Abstract: The Anaphase Promoting Complex (APC, also called APC/C) regulates cell cycle progression by forming two closely related, but functionally distinct E3 ubiquitin ligase sub-complexes, APCCdc20 and APCCdh1, respectively. Emerging evidence has begun to reveal that Cdc20 and Cdh1 have opposing functions in tumorigenesis. Specifically, Cdh1 functions largely as a tumor suppressor, whereas Cdc20 exhibits an oncogenic function, suggesting that Cdc20 could be a promising therapeutic target for combating human cancer. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
182
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 199 publications
(185 citation statements)
references
References 152 publications
(209 reference statements)
3
182
0
Order By: Relevance
“…CDC20-APC has been intensively studied in the cell cycle field and is viewed as a promising target in several human cancers (Wang et al, 2015). As proof of concept, conditional Cdc20 knockout in mouse models of skin cancer and fibrosarcoma caused mitotic arrest and apoptotic tumor regression (Manchado et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CDC20-APC has been intensively studied in the cell cycle field and is viewed as a promising target in several human cancers (Wang et al, 2015). As proof of concept, conditional Cdc20 knockout in mouse models of skin cancer and fibrosarcoma caused mitotic arrest and apoptotic tumor regression (Manchado et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…CDC20-APC has been viewed as a potential strategic target in several human cancers (Wang et al, 2015). CDC20 mRNA is elevated in glioblastoma compared to low-grade gliomas, and CDC20 immunoreactivity in gliomas correlates with pathological grade, but little is known about the biological roles of CDC20-APC in glioblastoma (Bie et al, 2011; Marucci et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence showed that Cdc20 exhibits an oncogenic function and targeting Cdc20 could be a novel strategy for combating human cancers [9, 48]. Notably, our results showed that prostate cancer-associated SPOP mutants including Y87C, F102C and W131G, which are clustered in its substrate-recruiting MATH domain, have lost the ability to bind and promote Cdc20 poly-ubiquitination and degradation (Figure 6).…”
Section: Discussionmentioning
confidence: 73%
“…In mitosis, APC activation requires binding of CDC20, which recognizes specific substrates and thereby drives the metaphase-anaphase transition and mitotic exit. 6 Increasing evidence suggests an oncogenic role for CDC20 in several human cancers. 6 Until recently, little was known about the functional significance of CDC20-APC in GBM.…”
mentioning
confidence: 99%
“…6 Increasing evidence suggests an oncogenic role for CDC20 in several human cancers. 6 Until recently, little was known about the functional significance of CDC20-APC in GBM. Recent studies in developmental neurobiology have revealed surprising non-mitotic roles for CDC20-APC in postmitotic neurons, suggesting the possibility that CDC20-APC controls functions beyond the cell cycle.…”
mentioning
confidence: 99%